A minimal cost analysis model for utilisation and capacity planning in surgical services. (1st January 2000) - Spangler, William E.; Strum, David P.; Vargas, Luis G.; May, Jerrold H.
This chapter explores cost reduction and capacity planning in surgical services. Classical operating suite (OR) utilisation is defined as the ratio of total OR time used to total OR time budgeted, but that definition of utilisation allows scheduling inefficiencies and costs to go undetected. Instead, a more accurate description of the overall use of resources can be achieved by dividing classical utilisation into under-utilisation and over-utilisation, and incorporating those measures within a minimal cost analysis model. The model, which was developed from a study of surgical case records collected over six years, indicates that the potential cost savings are significant.